PERANCANGAN SISTEM INFORMASI JASA LAUNDRY BERBASIS WEB PADA SYAM LAUNDRY - Abdullah Syam Paiso; Imam Yunianto (Jupiter: Journal of Computer & Information Technology, 2022)
The impact of technological developments is spoiling service companies. Laundry services at Syam Laundry Bekasi is a company engaged in laundry services. Syam Laundry does not use any computerized system to manage event data. Maintenance of customer data, event data, and delivery slips is still done manually, the solution to the Syam Laundry problem is to utilize web-based information technology in this system using the system development method, namely. a prototype of the Syam Laundry service information system can facilitate employee data entry by 66% to 100% in terms of recording transaction data and data security.